Profiling of Aerosols and Clouds over High Altitude Urban Atmosphere in Eastern Himalaya: A Ground-Based Observation Using Raman LIDAR - Trishna Bhattacharyya; Abhijit Chatterjee; Sanat K. Das; Soumendra Singh; Sanjay K. Ghosh (Atmosphere, 2023)
Profiles of aerosols and cloud layers have been investigated over a high-altitude urban atmosphere in the eastern Himalayas in India, for the first time, using a Raman LIDAR. The study was conducted post-monsoon season over Darjeeling (latitude 27°01<semantics>′</semantics> N longitude 88°36<semantics>′</semantics> E, 2200 masl), a tourist destination in north-eastern India. In addition to the aerosols and cloud characterization and atmospheric boundary layer detection, the profile of the water vapor mixing ratio has also been analyzed. Effects of atmospheric dynamics have been studied using the vertical profiles of the normalized standard deviation of RCS along with the water vapor mixing ratio. The aerosol optical characteristics below and above the Atmospheric Boundary Layer (ABL) region were studied separately, along with the interrelation of their optical and microphysical properties with synoptic meteorological parameters. The backscatter coefficient and the extinction coefficient were found in the range from <semantics>7.15×10−10</semantics> m<semantics>−1</semantics> sr<semantics>−1</semantics> to <semantics>3.01×10−5</semantics> m<semantics>−1</semantics> sr<semantics>−1</semantics> and from <semantics>1.02×10−5</semantics> m<semantics>−1</semantics> to <semantics>2.28×10−3</semantics> m<semantics>−1</semantics>, respectively. The LIDAR ratio varies between 3.9 to 78.39 sr over all altitudes. The variation of the linear depolarization ratio from 0.19 to 0.32 indicates the dominance, of non-spherical particles. The periodicity observed in different parameters may be indicative of atmospheric wave phenomena. Cloud parameters, such as scattering coefficients, top and bottom height, and optical depth for different cloud phases, have been evaluated. A co-located Micro Rain Radar has been used with LIDAR for cloud life cycle study.